The Effect Of Short-Term Debt And Long-Term Debt On Profitability In Manufacturing Companies Listed On The Indonesia Stock Exchange - Indah Rianti Panggabean (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2022)
This study aims to determine the effect of short-term debt and long-term debt on profitability. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange in 2017-2019. The number of samples used as many as 16 companies taken using purposive sampling technique. Data analysis used classical assumption test and multiple linear regression. The indicator for short term debt is short term debt (STD), long term debt indicator is long term debt equity ratio (LTDE), and profitability indicator is return on assets (ROA). The results of the research hypothesis are known that the t-test of the Short-Term Debt variable does not significantly affect Return On Assets, this can be seen from the significant value of 0.479 > 0.05 and the value of tcount > ttable or -0.079 < 2.014. And the Long-Term Debt has no significant effect on Return On assets, this can be seen from the significant value of 0.488 > 0.05 and the value of tcount > ttable or -0.292 > 2.014. Meanwhile, it simultaneously shows that the fcount value is 47.796 and ftable can be seen in the statistical table, it is obtained ftable = 3.20. So it can be concluded that fcount > ftable (47.796 > 3.20) and 0.368 > 0.05, meaning Ho is rejected and Ha is accepted. This means that short-term debt and long-term debt have a simultaneous effect on return on assets in the 2017-2019 period.